Análise proteômica do plasma de pacientes portadores de hepatocarcinoma - Freitas, Melissa Sanders (2016)
The liver cancer causes death more often than many other tumors because patients are usually diagnosed late. Hepatocellular carcinoma (HCC) is the primary most common type of liver cancer and represents, on average, 80% of all primary types of liver cancer. Thus, it is necessary to search for plasmatic biomarkers for early detection and diagnosis of HCC, method less invasive and easy to obtain. Abnormal glycosylation of some proteins arising from post-translational processing may be an indicator of pathologies, as well as inflammations and malignancies such as cancer. Thus, the glycoproteins are an important subject of study as biomarkers. One of the most used methods for detection of glycoproteins is through the use of lectins, which have high affinity for glycoconjugates. The frutalin, a tetrameric lectin from Artocarpus incisa seeds or "breadfruit", has an affinity for α-D-galactose residues and has been described as a potential lectin in biomedical applications. This paper proposes the search for potential biomarkers in cancer patients livers by comparing between the plasma of healthy individuals and patients with HCC. The plasma collected was imunodepletation and subsequently, serum glycoproteins were fractionated by affinity chromatography on Sepharose 4B matrix with immobilized frutalin, dialyzed, concentrated, and digested with trypsin for identification by mass spectrometry (MS). In total, they identified 19 proteins related directly or indirectly to the HCC and may present as potential biomarkers. Using the methodology engaging affinity chromatography with an immobilized plant lectin column and it was possible to provide a panel of candidate proteins to biological markers to assist in the early identification of patients with HCC, and thus increase the survival chances thereof, as well as to evaluate the use of a plant lectin fractionation of complex samples.